Price, trade size, and information revelation in multi-period securities markets - Ozsoylev, H; Takayama, S (2010)
We study price formation in securities markets, using the sequential trade framework of Glosten and Milgrom (1985). This paper makes one basic methodological advance over previous research on sequential securities trading: we allow traders to choose from n trade sizes in a multi-period market, where n can be arbitrarily large. We examine how trade size multiplicity affects the intertemporal dynamics of trading strategies, bid-ask spreads, and information revelation. We show that price impact, as a function of trade size, is increasing and exhibits (discrete) concavity.